2021
DOI: 10.3390/su131910819
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Factors Associated with Preventive Behaviors and Mental Health among Chinese Adults during the COVID-19 Pandemic Home Quarantine

Abstract: The outbreak of the coronavirus disease in 2019 (COVID-19) has greatly impacted the life and mental health of many people globally. The objective of this study was to investigate the factors associated with preventive behaviors and mental health among Chinese adults during their home quarantine in the COVID-19 period. An online questionnaire survey was administered in March 2020. The study participants were adults aged between 18 and 70 years old from 31 provinces in China. Of the 3878 participants, 1314 repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The scale was validated and translated into Serbian and has shown that the GAD-7 questionnaire is a viable measure of generalized anxiety disorder [30]. A score of 5 or above indicates the presence of anxiety, which is graded as mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), or severe (15 and above) [15]. The PHQ-2 questionnaire is a component of the PHQ-9 questionnaire; it consists of two items that measure the degree of depression patients have felt in the last two weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale was validated and translated into Serbian and has shown that the GAD-7 questionnaire is a viable measure of generalized anxiety disorder [30]. A score of 5 or above indicates the presence of anxiety, which is graded as mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), or severe (15 and above) [15]. The PHQ-2 questionnaire is a component of the PHQ-9 questionnaire; it consists of two items that measure the degree of depression patients have felt in the last two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…According to data obtained during the COVID-19 pandemic, higher levels of depression, anxiety, stress and burnout were reported [6,7] and especially in "essential" workers [8], e.g., healthcare workers [9]. In the literature there is evidence that those people working in nonessential activities, for example teachers, are prone to mental burden [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The crisis escalated to a public health emergency on 21st January, 2020 (Song et al, 2020). Since then, the Chinese government had employed strict public health measures, including locking down the epicenter of the outbreak, applying nationwide travel restrictions, and exercising home quarantine (Liu et al, 2021). There is a well-documented scholarly discourse on how the COVID-19 outbreak adversely affects the mental health of Chinese nationals (e.g., Li et al, 2020;Ren et al, 2020;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%